Fiscal decentralization after 20 years what have we learned? where do we go from here? - Diokno, Benjamin E. (2012)
Local government units (LGUs) in the Philippines have been given significant resources through grants (called internal revenue allotment or IRA) and taxing powers. But after 20 years, LGUs have become even more dependent on the IRA. A body of evidence suggests no sharp improvement in local public service delivery. The share of local budgets devoted to devolved functions has declined, due to creeping re-centralization of health and social welfare functions, increasing substitution of centrally controlled funds for local funds, and misplaced priorities on the part of local authorities.

The missing link in ensuring better delivery of devolved services is the weak process of accountability. The electoral process failed to hold local authorities accountable for their fiscal behavior. The generation of timely, relevant, and consistent information and indices of performance is the next challenge for better local public service delivery. Such information may be used by voters in holding local authorities accountable.

With the threat of a fiscal crisis due to the global slowdown, and with poverty rising, the march toward fiscal decentralization might be constrained. Between reducing poverty or deepening fiscal decentralization, policy makers are likely to choose the former.
Keywords: Decentralization in government; Local government; Revenue sharing; Internal revenue